Comparing Thoracic Extensive Laminoplasty (TELP) and Laminectomy in Treating Severe Thoracic Ligamentum Flavum Ossification: A Proposed Novel Technique and Case-Control Study. (21st April 2021) - Ma, Jun; Lu, Zhengyu; Zhou, Xin; Yin, Jia; Xu, Enjie; Jiang, Heng; Ma, Xiao; Meng, Yichen; Li, Zhilin; Gao, Rui; Lin, Tao; Zhou, Xuhui
Abstract : Objective . (1) To propose a novel technique named thoracic extensive laminoplasty (TELP) in curing severe thoracic ligamentum flavum ossification (STOLF) and (2) to compare outcomes between TELP and laminectomy in curing STOLF. Methods . Cases with fused or tuberous STOLF (Sato classification) treated from Jan 2015 to Jan 2017 were reviewed and divided into the TELP group (G1) and laminectomy group (G2) according to their surgical management. Data on demographics, complications, pre- and postoperative symptoms, residual spinal canal area (RSCA-1), residual spinal cord area (RSCA-2), modified Japanese Orthopedic Association score (mJOA), and health-related quality of life (HRQOL, based on the SF-36) were collected. Results . Fifty-nine G1 and sixty-two G2 patients were enrolled. No significant differences in demographic data or preoperative data of RSCA-1, RSCA-2, mJOA, or HRQOL were observed between the two groups (p > 0.05 ). Patients in G1 and G2 showed similar postoperative improvements in RSCA-1 and RSCA-2 at the final follow-up (p > 0.05 ). However, patients in G1 showed higher postoperative improvements in mJOA (OR = 2.706, 95% CI: 1.279~5.727, p = 0.008 ) at the final follow-up. Patients in G1 also showed higher postoperative improvements in HRQOL than patients in G2 (p < 0.05 ) at the final follow-up, and patients with more severe STOLF presented with better improvements in HRQOL in G1 (p < 0.05 ). Dural laceration and cerebrospinal fluid leakage were observed in seven G2 patients, and no complications were found in G1 patients after surgery. Conclusion . TELP is a novel, effective, and safer surgical technique in treating STOLF and could be a substitute for traditional laminectomy.